2009
DOI: 10.3109/14767050903410631
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic weight estimation in large for gestational age fetuses: A comparison of 17 sonographic formulas and four models algorithms

Abstract: Accuracy of EFW in LGA fetuses is attributable to the biometric parameters used. Our findings show that the best formulas for EFW are those which only consider the abdominal measurements, especially in diabetic mothers. The new variable that we propose (HPT) confirms this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
1
17
0
3
Order By: Relevance
“…Notably, however, mathematical models may not be feasible in a clinical practice setting. Taken together, available research supports ultrasound measurement alone not being an accurate predictor of estimated fetal weight, and maternity care providers should consider this when counseling women …”
Section: Methods Of Estimating Fetal Weightmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, however, mathematical models may not be feasible in a clinical practice setting. Taken together, available research supports ultrasound measurement alone not being an accurate predictor of estimated fetal weight, and maternity care providers should consider this when counseling women …”
Section: Methods Of Estimating Fetal Weightmentioning
confidence: 94%
“…A 2010 review of sonographic models and algorithms concluded that the widely accepted Hadlock formula that includes biparietal diameter, abdominal circumference, and femur length, produces an estimated fetal weight that is acceptable; however, the Warsof2 formula that uses the abdominal circumference alone, showed a higher accuracy in the predication of large‐for‐gestational age fetuses. Specifically, the Warsof2 formula demonstrated the highest accuracy (mean percentage error) and precision (standard deviation, SD) for predicting fetal macrosomia with overall prediction within 5%, 10%, and 15% of birth weight in 68%, 94%, and 98% of actual birth weight, respectively …”
Section: Methods Of Estimating Fetal Weightmentioning
confidence: 99%
“…AC is the most common and reliable single parameter used to assess risk of macrosomia (56) . It is measured on a defined plane incorporating the liver since growth abnormalities are often reflected by changes in liver size (57) .…”
Section: Ultrasound Assessmentmentioning
confidence: 99%
“…Muitos estudos salientam que os modelos para estimativa de peso fetal deveriam ser adaptados às diferentes populações, respeitando suas características étnicas [9][10][11][12][13][14][15] . No entanto, a maioria dos centros utiliza fórmulas tradicionais geradas em outros países, que podem levar a erros significativos quando aplicadas localmente 14,15 .…”
Section: Introductionunclassified
“…No entanto, a maioria dos centros utiliza fórmulas tradicionais geradas em outros países, que podem levar a erros significativos quando aplicadas localmente 14,15 . Além disso, a avaliação do tamanho do feto (estimativa do peso em um momento da gestação) é frequentemente considerada como sinônimo de avaliação de crescimento, sendo esta interpretada erroneamente à luz de intervalos de referência provenientes de estudos transversais 16,17 .…”
Section: Introductionunclassified